Estratégias de leitura e o ensino do ato de ler - Souza , Silvana Paulina de [UNESP] (2014)
This work on the act of reading had its genesis during the master's research, which focused on the organization of the pedagogical context for the appropriation of writing. Because of my concerns about the process of appropriation of reading for children of elementary school - Cycle I , the need for tools and resources that make up the organization of educational activities for appropriation of written language is thinking, specifically related to reading . Thus, the research aimed to create contexts and motivators for teaching reading comprehension strategies modes and thus contribute to the formation of the child reader . The thesis is that the approach of reading strategies intentionally organized creates the need for teaching the act of reading context. Metacognitive actions on the act of reading causes the student to think about what he reads, how and for what reads and promotes understanding of the text read and the appropriation of their contents. With methodological basis in the formative experiment, the data were generated in the implementation of strategies for reading comprehension while developing projects produced through reading and recordings, logbook, weekly, notes and photographs of students. The subjects and the research field belonged to a school of the municipal elementary schools of a city in the countryside, where the researcher had the role of a teacher. Two groups participated in the research process a group of third grade, in 2012, and a group of fourth grade in 2013, with the same students in three semesters of work . Considering the activity of the children and their ability to learn and develop; the school as a formal education, experiences and pedagogical choices, and the teacher as creator of mediation in the settlement process the knowledge, the Cultural-Historical Theory guided the work and enabled forming links with other proposals that address the reading and learning of the act of reading with strategies...